Diamond Crystals - Yuri N. Palyanov (Ed.)
This Special Issue is intended to serve as an interdisciplinary forum covering broad aspects of the science, technology, and application of synthetic and natural diamonds. The issue contains 13 papers, which highlight recent investigations and developments in diamond research related to the diverse problems of natural diamond genesis, diamond synthesis and growth using CVD and HPHT techniques, and the use of diamond in both traditional applications, such as mechanical machining of materials, and the new recently emerged areas, such as quantum technologies. The results presented in the contributions collected in this special issue clearly demonstrate that diamond occupies a very special place in modern science and technology.